Beyond this moment eaudiobook Timber ridge reflections series, book 2. - Alexander, Tamera (Timber Ridge Reflections, 2013)
Tamera Alexander-RITA and Christy Award winner-interweaves threads of hope and second chances into a life tangled by half-truths and lies. Stepping off the train in 1876 Colorado Territory, Professor Molly Whitcomb, Ph.D, makes a distasteful choice she sees as her only chance to recover a fraction of what she's lost. "Plot twists will keep you turning pages long into the night."-Romantic Times